Program Lansia Sabar Berbasis Reminiscence dan Terapi Seni untuk Menurunkan Kecemasan pada Lansia Penyandang Diabetes Melitus Tipe II - Errina Puspitasari; Sofia Retnowati (Faculty of Psychology, Universitas Gadjah Mada, 2016)
This “Lansia Sabar” program which is consisted of reminiscence and art therapy is expected to facilitate the elderly to look back on their lives positively. This programm was administered to nine (9) elderly with type II diabetes mellitus aged 55-70 years who show moderate to severe levels of anxiety. Anxiety level is measured using Beck Anxiety Inventory (BAI). The program lasts for six meetings with a maximum duration of 120 minutes for each session. The experimental design using one-group pretest-posttest with additional double pretest. Data will be analyzed quantitatively using the friedman test, with the additional descriptive data analysis on the results of observation, task book, and the visual inspection. The Friedman test showed Fr(2) = 5,200, p = 0,074 (p > 0,05). It showed that “Lansia Sabar” program has no significant effect to decrease anxiety in the elderly with type II diabetes mellitus.